Speech evaluation in children with temporomandibular disorders (Journal of Applied Oral Science, 2011)
OBJECTIVE: The aims of this study were to evaluate the influence of temporomandibular disorders (TMD) on speech in children, and to verify the influence of occlusal characteristics. MATERIAL AND METHODS: Speech and dental occlusal characteristics were assessed in 152 Brazilian children (78 boys and 74 girls), aged 8 to 12 (mean age 10.05 ± 1.39 years) with or without TMD signs and symptoms. The clinical signs were evaluated using the Research Diagnostic Criteria for TMD (RDC/TMD) (axis I) and the symptoms were evaluated using a questionnaire. The following groups were formed: Group TMD (n=40), TMD signs and symptoms (Group S and S, n=68), TMD signs or symptoms (Group S or S, n=33), and without signs and symptoms (Group N, n=11). Articulatory speech disorders were diagnosed during spontaneous speech and repetition of the words using the "Phonological Assessment of Child Speech" for the Portuguese language. It was also applied a list of 40 phonological balanced words, read by the speech pathologist and repeated by the children. Data were analyzed by descriptive statistics, Fisher's exact or Chi-square tests (α=0.05). RESULTS: A slight prevalence of articulatory disturbances, such as substitutions, omissions and distortions of the sibilants /s/ and /z/, and no deviations in jaw lateral movements were observed. Reduction of vertical amplitude was found in 10 children, the prevalence being greater in TMD signs and symptoms children than in the normal children. The tongue protrusion in phonemes /t/, /d/, /n/, /l/ and frontal lips in phonemes /s/ and /z/ were the most prevalent visual alterations. There was a high percentage of dental occlusal alterations. CONCLUSIONS: There was no association between TMD and speech disorders. Occlusal alterations may be factors of influence, allowing distortions and frontal lisp in phonemes /s/ and /z/ and inadequate tongue position in phonemes /t/; /d/; /n/; /l/.